Нова верхньопалеолітична стоянка Оболоння - Ступак, Д.В.; Хлопачев, Г.А.; Грибченко, Ю.М.; Комар, М.С. (Археологический альманах, 2014)
В статті висвітлюються матеріали досліджень нововиявленої верхньопалеолітичної стоянки Оболоння у Подесенні. Obolonnya is the new Upper Palaeolithic site which was discovered in 2010. It is the southernmost location of the Upper Palaeolithic in the Middle Desna region, and it is the first site with Aurignacian features in artefacts assemblage in the territory of Northern Ukraine. The results of environmental studies, as well as the characteristic features of stone and mammoth tusk assemblages make a date 20730 ± 120 BP (OxA-28035) more acceptable. Thus, Obolonnya is the first manifestation of Epiaurignacian industry in the Middle Desna region and together with sites of Pushkari group is the one of the oldest settlement in this territory. Obtained results are extremely important for the understanding of cultural processes in the Eastern European Upper Palaeolithic, and particularly for the understanding of Epigravettian origin in Dnipro region.